Feedlot feeding improves beef productivity and lowers methane intensity in Tanzania - Gurmu, Endale; Arndt, Claudia; Slater, Annabel (International Livestock Research Institute, 2025)
This blog presents results from a beef feedlot study in Tanzania showing that improved feeding strategies can substantially increase animal productivity while reducing methane emissions intensity. The findings demonstrate how targeted feed interventions can improve efficiency and lower greenhouse gas emissions per unit of output, contributing to climate-smart livestock production in emerging beef systems.